Matrix Remodeling and Hyaluronan Production by Myofibroblasts and Cancer-Associated Fibroblasts in 3D Collagen Matrices - Jiranuwat Sapudom; Claudia Damaris Müller; Khiet-Tam Nguyen; Steve Martin; Ulf Anderegg; Tilo Pompe (Gels, 2020)
The tumor microenvironment is a key modulator in cancer progression and has become a novel target in cancer therapy. An increase in hyaluronan (HA) accumulation and metabolism can be found in advancing tumor progression and are often associated with aggressive malignancy, drug resistance and poor prognosis. Wound-healing related myofibroblasts or activated cancer-associated fibroblasts (CAF) are assumed to be the major sources of HA. Both cell types are capable to synthesize new matrix components as well as reorganize the extracellular matrix. However, to which extent myofibroblasts and CAF perform these actions are still unclear. In this work, we investigated the matrix remodeling and HA production potential in normal human dermal fibroblasts (NHFB) and CAF in the absence and presence of transforming growth factor beta -1 (TGF-β1), with TGF-β1 being a major factor of regulating fibroblast differentiation. Three-dimensional (3D) collagen matrix was utilized to mimic the extracellular matrix of the tumor microenvironment. We found that CAF appeared to response insensitively towards TGF-β1 in terms of cell proliferation and matrix remodeling when compared to NHFB. In regards of HA production, we found that both cell types were capable to produce matrix bound HA, rather than a soluble counterpart, in response to TGF-β1. However, activated CAF demonstrated higher HA production when compared to myofibroblasts. The average molecular weight of produced HA was found in the range of 480 kDa for both cells. By analyzing gene expression of HA metabolizing enzymes, namely hyaluronan synthase (HAS1-3) and hyaluronidase (HYAL1-3) isoforms, we found expression of specific isoforms in dependence of TGF-β1 present in both cells. In addition, HAS2 and HYAL1 are highly expressed in CAF, which might contribute to a higher production and degradation of HA in CAF matrix. Overall, our results suggested a distinct behavior of NHFB and CAF in 3D collagen matrices in the presence of TGF-β1 in terms of matrix remodeling and HA production pointing to a specific impact on tumor modulation.